ANISOTROPIC STELLAR WIND IN CLOSE BINARIES WITH NON-RELATIVISTIC COMPONENTS: OBSERVATIONAL EVIDENCES AND THEORETICAL IMPLICATIONS - Pustylnik, I. (Одеські астрономічні публікації, 2017)
Some of the most important issues of anisotropic stellar wind research in close binaries with non-relativistic components, basically Algol-type stars, serpentides and early-type contact systems are briefly discussed with an emphasis on the problems of origin of anisotropy, morphology of gas, observable effects of wind upon spectra and light curves, the angular momentum loss and the evolutionary consequences.